The Possibility of Balancing VOC Concentration Fluctuations by a Flow through an Activated Carbon Bed - Jan Červenka; Tereza Moravcová; Lucie Obalová (Adsorption Science & Technology)
Waste gases from periodic processes often contain VOC concentrations which fluctuate significantly. This causes trouble during their cleaning, for example by thermal destruction. A simple experiment has demonstrated that such concentration fluctuations can be dampened by flowing the polluted gas through a layer of adsorbent. Measurements of balancing the concentration fluctuations of triethylamine (TEA) by flowing through an activated carbon bed showed that balancing average TEA inlet concentrations of 7–30 g/m 3 occurs at a superficial velocity lower than 4–0.6 cm/s, which corresponds to a residence time of 37–250 s. An important notion is that balancing the fluctuations may be achieved independently of dividing the time of TEA presence in the inlet air if the given average 8 h TEA concentration at the inlet can be retained.